Program peningkatan pemanfaatan instrumentasi laboratorium olimpiade sains terpadu di MAN 2 Kudus sebagai upaya optimalisasi aset Madrasah untuk pendidikan dan penelitian - Harjono; Alauhdin, Mohammad; Kurniawan, Cepi; Sulistyani, Martin; Huda, Nuril; Prasetyo, Ridho (IKIP SILIWANGI, 2024)
Laboratory instrumentation needs to be comprehensively understood by researchers to be used effectively, efficiently, and safely. This knowledge and competence have the potential to generate high-quality research topics. This community service activity aims to enhance the knowledge and competence of the academic community of MAN 2 Kudus in operating laboratory instruments to support high-quality research, as well as optimizing the school's assets for education and research. The methods employed in this community service include: 1) observation, 2) identification of laboratory instrumentation, 3) preparation and monitoring of laboratory instrumentation, and 4) workshops and mentoring. The implementation of the community service program is carried out in stages with a systematic approach, covering: explaining the basic concepts of instrument usage and data analysis methods, demonstrating the use of instruments, hands-on practice, evaluation and feedback, documentation and references, and strengthening materials related to soft skills and hard skills for conducting research in the laboratory. The assessment results show that the skills in operating laboratory instrumentation of the academic community of MAN 2 Kudus have improved. The workshops and mentoring activities have broadened the participants' insights in preparing efficient, safe, and applicable research. Through this community service, it is hoped that the soft skills and hard skills acquired by the academic community can be consistently developed and maintained to enhance the branding value of MAN 2 Kudus in future Olympiads and scientific writing competitions.